Antibiofilm Potential of Silver Sulfadiazine-Loaded Nanoparticle Formulations: A Study on the Effect of DNase-I on Microbial Biofilm and Wound Healing Activity - Patel K.K.; Surekha D.B.; Tripathi M.; Anjum M.M.; Muthu M.S.; Tilak R.; Agrawal A.K.; Singh S. (My University, 2025)
Biofilm resistance is one of the severe complications associated with chronic wound infections, which impose extreme microbial tolerance against antibiotic therapy. Interestingly, deoxyribonuclease-I (DNase-I) has been empirically proved to be efficacious in improving the antibiotic susceptibility against biofilm-associated infections. DNase-I hydrolyzes the extracellular DNA, a key component of the biofilm responsible for the cell adhesion and strength. Moreover, silver sulfadiazine, a frontline therapy in burn wound infections, exhibits delayed wound healing due to fibroblast toxicity. In this study, a chitosan gel loaded with solid lipid nanoparticles of silver sulfadiazine (SSD-SLNs) and supplemented with DNase-I has been developed to reduce the fibroblast cytotoxicity and overcome the biofilm-imposed resistance. The extensive optimization using the Box-Behnken design (BBD) resulted in the formation of SSD-SLNs with a smooth surface as confirmed by scanning electron microscopy and controlled release (83%) for up to 24 h. The compatibility between the SSD and other formulation excipients was confirmed by Fourier transform infrared, differential scanning calorimetry, and powder X-ray diffraction studies. Developed SSD-SLNs in combination with DNase-I inhibited around 96.8% of biofilm of Pseudomonas aeruginosa as compared to SSD with DNase-I (82.9%). In line with our hypothesis, SSD-SLNs were found to be less toxic (cell viability 90.3 ± 3.8% at 100 μg/mL) in comparison with SSD (Cell viability 76.9 ± 4.2%) against human dermal fibroblast cell line. Eventually, the results of the in vivo wound healing study showed complete wound healing after 21 days' treatment with SSD-SLNs along with DNase-I, whereas marketed formulations SSD and SSD-LSNs showed incomplete healing after 21 days. Data in hand suggest that the combination of SSD-SLNs with DNase-I is an effective treatment strategy against the biofilm-associated wound infections and accelerates wound healing. © 2019 American Chemical Society.